The Changing Structure of Africa’s Economies - Diao, Xinshen (Published by Oxford University Press on behalf of the World Bank, 2018)
Using data from the Groningen Growth and Development Center’s Africa Sector Database and the Demographic and Health Surveys, we show that much of Africa’s recent growth and poverty reduction has been associated with a substantive decline in the share of the labor force engaged in agriculture. This decline is most pronounced for rural females over the age of 25 who have a primary education; it has been accompanied by a systematic increase in the productivity of the labor force, as it has moved from low productivity agriculture to higher productivity services and manufacturing. We also show that, although the employment share in manufacturing is not expanding rapidly, in most of the low-income African countries the employment share in manufacturing has not peaked and is still expanding, albeit from very low levels. More work is needed to understand the implications of these shifts in employment shares for future growth and development in Africa south of the Sahara.